Rethinking the Role of Customary Elites: The Flexibility of Adat and the Interest of Customary Elites in Local Politics in Lampung, Indonesia - Kaneko, Masanori; Nurdin, Bartoven Vivit; Sari, Ifaty Fadliliana; Asnani; Turki, Syifaa Sabianova Addina; Thesalonica, Denysha (Research and Development Agency Ministry of Home Affairs, 2024)
This study examines the customary elites' role in the local socio-political landscape in Lampung, Indonesia. The problem is that so far, the role of customary elites is often ignored in regional development, where they only become political symbols and are used for local political interests in the region. In this case study, customary elites attempt to manage their adat communities so that they make positive contributions to society. Adat still has a significant influence and plays an important role in the daily lives of the Lampung people. However, this is not just community-level regulation or customary law; it also has important cultural and social significance for the nation. This study uses qualitative research methods and an ethnographic approach. Data was collected through in-depth interviews and participant observation with analysis using data reduction, verification, data display, and data triangulation. The result showed that adat helps form and maintain social ties among local communities, contributing to government development programs and administrative changes. In the adat government, traditional elites also represent their adat communities. Adat shows flexibility towards change while preserving local wisdom and contributing to regional development. Customary elites and adat communities have great influence in society, and they are valued and respected by their collective members. Their role should be maximized by local governments in regional development because one of the keys to successful development is utilizing local wisdom because local wisdom is the element that is most adaptable and flexible in change.